الاقتصاد الموازي وأثره على النمو الاقتصادي في الجزائر دراسة قياسية للفترةالممتدة من 1990الى 2019 - سلطاني, عادل; دادن, عبد الغني (جامعة الوادي - University of Eloued, 2021)
The aim of this study is the assessment of the impact of the parallel economy on Algeria's economic growth from 1990 to 2019 through the economicmeasurement methods that use the Autoregressive Distributed Lag model (ARDL). In conclusion, this study resulted that the parallel economy has a positive impact on economic growth in the short and long term
The effect of parralel economy on economic development indexes in Algeria economitric study during the period of 1990 to 2019
مقال
Keywords: الاقتصاد الموازي ; نموذج الانحدار الذاتي للفجوات الزمنية الموزعة المتباطئة ; النمو الاقتصادي ; البطالة ; التضخم